Appreciative inquiry change at the speed of imagination - Watkins, Jane Magruder (Practicing organization development series ;, 2011)
"This book shows how the Appreciative Inquiry process helps OD and HR professionals tap into inspiring "high point" accounts of personal or collective capacity. This new edition puts the focus on how AI really works and adds guidelines on how to apply AI in a variety of organizational situations and for a variety of initiatives such as coaching, leadership development, strategic planning, and teambuilding. It contains tools and other resources to help with immediate use in the workplace and new and updated case studies that show how it really works."--